From Screen to Table: Understanding Customer Intentions in GrabFood Adoption - Sandra, Oky Puspita; Nasution, Muhammad Dharma Tuah Putra; Harahap , Ramadhan (International Journal of Business, Law, and Education, 2024)
This study investigates how perceived usefulness, perceived convenience, and various food choices impact customers' intentions to adopt food delivery services via the GrabFood application. The research methodology involved a survey utilizing questionnaires for data collection. Regression analysis findings reveal that perceived usefulness, perceived convenience, and various food choices significantly influence customer intentions. Both perceived usefulness and convenience positively and significantly affect customer intentions, while various food choices also wield a notable influence. These results contribute to theoretical comprehension by furnishing empirical evidence of the interaction among these factors and customer intentions, thereby advancing the theoretical framework of technology acceptance and consumer behavior. The practical implications are outlined within this study.